Single-cell RNA sequencing identifies CXADR as a fate determinant of the placental exchange surface - Dafina M. Angelova; Aleksandra Tsolova; Malwina Prater; Noura Ballasy; Wendi Bacon; Russell S. Hamilton; Danielle Blackwell; Ziyi Yu; Xin Li; Xin Liu; Myriam Hemberger; D. Stephen Charnock-Jones (Nature Communications)
Abstract The placenta is the critical interface between mother and fetus, and consequently, placental dysfunction underlies many pregnancy complications. Placental formation requires an adequate expansion of trophoblast stem and progenitor cells followed by finely tuned lineage specification events. Here, using single-cell RNA sequencing of mouse trophoblast stem cells during the earliest phases of differentiation, we identify gatekeepers of the stem cell state, notably Nicol1, and uncover unsuspected trajectories of cell lineage diversification as well as regulators of lineage entry points. We show that junctional zone precursors and precursors of one of the two syncytial layers of the mouse placental labyrinth, the Syncytiotrophoblast-I lineage, initially share similar trajectories. Importantly, our functional analysis of one such lineage precursor marker, CXADR, demonstrates that this cell surface protein regulates the differentiation dynamics between the two syncytial layers of the mouse labyrinth, ensuring the correct establishment of the placental exchange surface. Deciphering the mechanisms underlying trophoblast lineage specification will inform our understanding of human pregnancy in health and disease.